FEASIBILITY STUDY FOR THE ESTABLISHMENT OF THE CENTER FOR DATA SCIENCE STUDIES AT UIN SUNAN KALIJAGA YOGYAKARTA - Riyanto, Muhamad Zaki (Universitas Negeri Yogyakarta, 2023)
With the rapid development of data science research and its more comprehensive application, and to support the integration-interconnection adopted by UIN Sunan Kalijaga Yogyakarta, it is necessary to have an institution overseeing it. This article discusses the feasibility study of establishing a Center for Data Science Studies using SWOT analysis. Furthermore, it discusses the ideal profile of the Center for Data Science Studies, including organizational management, activities management, resource management, and financial management.